Indonesia Pengembangan Instrumen Soal Berorientasi Praktek Keterampilan Pemecahan Masalah Materi Laju Reaksi - Minatus, Wahyuni; Drastisianti, Apriliani; Mulyanti, Sri (Jurnal Riset Pendidikan Kimia (JRPK), 2023)
The question instrument on the reaction rate material contains two competencies, namely understanding concepts and counting to help students who can increase the enthusiasm of students' learning activities. The method used in this study refers to the 4D development model proposed by Thiagarajan (1974). The 4D development model has 4 stages, namely define, design, develop, and disseminate. In this study, it was shown that the question instrument developed had a good interpretation so that it was able to make students understand more about the concept of material on the rate of reaction.